Consumer payment choice for bill payments - Claire Greene; Joanna Stavins (Federal Reserve Bank of Boston, 2020)
Why do US consumers pay their bills the way they do? Using data from a recent diary of consumer payment behavior, we find that the type of bill consumers are paying and how they are paying (online or automatically) are important factors in determining the payment method, in addition to the dollar value of the bill and the demographic and income profile of the individual who is paying. In contrast, dollar value and demographic attributes are found to be the most important factors determining the payment instrument chosen for purchases. Consumer choices for bill payments are somewhat constrained by requirements imposed by merchants, while the choice of payment instrument for purchases is not constrained by such requirements.The convenience and speed provided by automatic and online payments are not benefitting all US consumers equally. Unbanked consumers lack access to most payment methods and, hence, use cash or prepaid cards to pay their bills. Low-income consumers pay their bills differently from the rest of the sample: They are more likely to pay in person, use significantly more cash, and are less likely to set up automated or online bill payments, regardless of whether they have a bank account. Although consumers specify in the diary which methods they prefer to use to pay their bills, in practice they are not likely to act consistently with their stated preferences. We find that consumers who pay their bills online are less likely to deviate from their preferred payment method, while those who pay their bills automatically are more likely to deviate, after we control for income, demographic attributes, the dollar amount of the bill, and the merchant type. We find no evidence of the salience effect of automatic bill payments that Sexton (2015) finds for energy consumption. Rather, we find that consumers who pay their bills automatically have higher incomes and spend more on bills than lower-income consumers do, but that automatic bill payments are lower in value on average, which is the opposite of the finding by Sexton (2015).
Keywords: D12; D14; E42; 330; bill payments; payment choice; payment preferences; consumer payments